PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN KOMPENSASI TERHADAP KINERJA DOSEN POLITEKNIK PARIWISATA MAKASSAR DALAM MELAKSANAKAN TRI DARMA PERGURUAN TINGGI - Muhammad Said; Muhammad Ide Said; Andi Jam'an (COMPETITIVENESS, 2020)
This study aimed to determine and analyze the influence of leadership, organizational commitment, and compensation on the performance of lecturers as well as to find out and analyze the influence of the dominant variables effecting the Performance of Makassar Tourism Polytechnic Lecturer in implementing Higher Education Tridarma.. The study was conducted at the Makassar Tourism Polytechnic for three months, from January 2019 - March 2019 with a population were 78 people, because the population is small, this study applied the census method. The samples taken were all members of the existing population. The questionnaire was given to all 78 lecturers of the Makassar Tourism Polytechnic. The analytical method used in this study was a quantitative descriptive method, with a double regression test preceded by conducting a validity and reliability test of the question items for each variable and assumption test. The results of this study indicate that: 1) Leadership has no significant positive influence on performance with P = 0.947 0.05 with a coefficient value of 0.013, this coefficient indicates that the leadership model applied to Makassar Tourism Polytechnic has not been able to improve the performance of Makassar Tourism Polytechnic lecturers in implementing Higher Education Tridarma; 2) Organizational commitment has a significant positive influence on performance with P = 0.010 0.05 with a coefficient value of 0.535, this coefficient indicates that better the organizational commitment, the better the performance will be; 3) Compensation has a significant positive influence on performance with P = 0.001 0.05 with a coefficient value of 0.613, this coefficient indicates that better compensation the lecturer has, the lecturer's performance will increase; and 4) Compensation with a dominant influence on the performance of this can be seen from the beta value of 0.474 greater than other variables. Keywords: Compensation.